Chemical and Functional Characterisation of Cranberry Extract: A Focus on Polyphenolic Content and Stabilisation Strategies - Veledar-Hamalukić, Anisa; Pramenković, Emina (Scripta Medica, 2025)
Background/Aim: Cranberry (Vaccinium macrocarpon, Aiton) extracts are widely utilised in dietary supplements due to their rich content of polyphenolic compounds, particularly anthocyanins and proanthocyanidins (PACs), which are associated with antioxidative and antimicrobial activities. However, commercial products often lack detailed phytochemical characterisation, raising concerns about efficacy and stability, especially in the presence of additives such as vitamin C. This study aimed to characterise the polyphenolic content of a commercial dry cranberry extract by quantifying its anthocyanins and PACs using both the 4-dimethylaminocinnamaldehyde (DMAC) and modified Bate-Smith assays to explore potential stabilising agents for improved extract stability. Methods: Anthocyanins and vitamin C were quantified using HPLC-DAD. PACs were quantified using two complementary colorimetric methods: DMAC (with catechin chloride as standard) and a modified Bate-Smith method (with procyanidin B2 standard). Antioxidative activity was assessed using DPPH and ABTS assays. Literature-based evaluation of succinate and glutamate was conducted to assess their potential as polyphenol stabilisers. Results: Five major anthocyanins were identified, with total content of 9.95 mg/g. PAC content was determined as 53.57 % via DMAC and 36.31 % via Bate-Smith, underscoring the impact of method selection. Antioxidant assays confirmed strong activity (IC50 = 110 µg/mL ABTS, 92.85 µg/mL DPPH). Vitamin C content was low (1.2 mg/g), consistent with extract maturity. Literature suggests that succinate, due to its diacidic nature, may provide enhanced stabilisation compared to other additives. Conclusion: Analysed cranberry extract was rich in bioactive polyphenols and exhibited significant antioxidant potential. The comparison of analytical methods highlights the need for standard harmonisation. Stabilisation strategies such as succinate addition should be further evaluated to enhance the shelf-life and efficacy of cranberry-based nutraceuticals.